Prospects of radical innovation in Brazil - Torres, Lívia Abreu; Freitas, Leonardo Sousa de (Science & Technology Journals, 2019)
The purpose of this article is to present a mapping of the national scientific yield on the radical innovation theme, highlighting gaps and opportunities for future research. A bibliometric survey of the articles related to the topic in the main Brazilian journals according to WebQualis 2015 standard was carried out, without establishing a temporal cut, and 16 articles were identified. The research is descriptive, with quantitative and qualitative approaches, with analyses performed through SPSS software and manual content analysis. The results showed low national scientific yield and lack of quantitative approaches. The most cited authors were identified in the themes innovation and radical innovation, and an overview on the covered topics was provided, including contributions of the authors researched and suggestions for future research.